Household indebtedness in the European Union countries: Going beyond the mainstream interpretation - Ricardo Barradas; Inês Tomás (PSL Quarterly Review, 2023)
This paper develops a panel data econometric analysis in order to determine the main macroeconomic causes of household indebtedness in the European Union countries from 1995 to 2019. During that time, household indebtedness reached unprecedented and unsustainable levels, which played a crucial role in the emergence of the last financial and economic crisis. This is not clearly well interpreted by the mainstream economics, which advocates that household indebtedness is just an instrument to smooth consumption in a continuous process of utility maximization over life. This paper estimates a model according to which the household indebtedness depends on seven mainstream and non-mainstream macroeconomic causes, namely housing prices, financial asset prices, personal income inequality, the households' labour income, welfare state expenditures, the working-age population and interest rates. This paper finds that housing prices, welfare state expenditures and interest rates impact positively on household indebtedness in the European Union countries, whilst the financial asset prices, personal income inequality and households' labour income impact negatively on household indebtedness in the European Union countries. This paper also finds that the fall of household labour income and the rise of the housing prices have been the main triggers of household indebtedness in the European Union countries since 1995.
Keywords: C23; D10; E21; R20; 330; European Union; household indebtedness; panel data; fixed effect two-stage least squares